Tamm Plasmons: Properties, Applications, and Tuning with Help of Liquid Crystals - Victor Yu. Reshetnyak; Igor P. Pinkevych; Michael E. McConney; Timothy J. Bunning; Dean R. Evans (Crystals)
This article provides a brief overview of the research on localized optical states called Tamm plasmons (TPs) and their potential applications, which have been extensively studied in recent decades. These states arise under the influence of incident light at the interface between a metal film and a medium with the properties of a Bragg mirror, or between two media with the properties of a Bragg mirror. The localization of the states in the interfacial region is a consequence of the negative dielectric constant of the metal and the presence of a photonic band gap of the Bragg reflector. Optically, TPs appear as resonant reflection dips or peaks in the transmission and absorption spectra in the region corresponding to the photonic band gap. The relative simplicity of creating a Tamm structure and the significant sensitivity of TPs to its parameters make them attractive for applications. The formation of broadband and tunable TP modes in hybrid structures containing, in particular, rugate filters and porous distributed Bragg reflectors are considered. Considerable attention is paid to TP designs that include liquid crystals, which allow for the remote tuning of the TP spectrum without the mechanical restructuring of the system. The application of TPs in sensors, thermal emitters, absorbers, laser generation, and the experimental capabilities of TP-liquid crystal devices are also discussed.